An Unrecorded Decay in Living Deodar - Bakshi, B. K.; Ram Reddy, M. A.; Singh, Balwant (Indian Forester, 1970)
A serious butt and trunk rot in living deodar (Cadrus dendara Loudon) was recorded in a pure deodar plantation clear fel1ed in 1967 in Aleo Bihal, Manali, Kulu Forest Division, H.P. State. About 56 per cent trees and 24 per cent stumpage area showed decay. In roots located in between boulders, cracks may have appeared due to inadequate space during their development. The decay fungus possibly entered through such injuries. Sporophores associated with decay could not be seen on fresh deodar stumps on the site clear felled in 1967 or old stumps on a similar site clear felled in 1935. The decay fungus was isolated in culture and described. In cultures, perfect fruiting bodies developed from which the fungus could be identified as Peviaphara luna Romell. The sporophores of this fungus produced in nature are present in the herbarium and were collected during earlier years on associated deodar logs showing brown, cuboidal decay. The significence of decay in deodar in cross cutting of logs to different sizes eliminating the decayed portions and also in the healthy growth of trees replanted on such bouldery sites are discussed.